Catabolic response profiles, catabolic uniformity and richness as microbiological indicators in a soil of Pergamino, Buenos Aires Province, with and without previous application of glyphosate - Ríos, Ruth Paola (2016)
Fil: Ríos, Ruth Paola. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.